Effects of Pre-Reading Study and Reading Exposure on the Learning and Processing of Collocations - Dilorom Poyonova; Sevara Abdishukurova; Makhliyo Shomurodova (Scientific Trends, 2025)
Little is known about how pre-reading activities influence the learning of word combinations, known as collocations. This study investigated the impact of pre-reading study and reading exposure on processing and learning new collocations using eye-tracking and tests measuring recall and recognition. Three methods were compared: reading-only, where the target phrases were included in sentences; study-only, where learners explicitly studied the phrases; and pre-reading study plus reading, where learners studied the phrases before encountering them in sentences. The results showed that pre-reading study plus reading was the most effective method, followed by reading-only, which outperformed study-only. Studying collocations before reading helped learners pay more attention to them during reading, and greater attention during the pre-reading study phase, as indicated by eye fixations, was linked to better learning outcomes.